Studies on Synergistic Effects of Thermal Treatment on Physicochemical Properties of Starch Blends (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The aim of the study was to evaluate the potential synergistic effect of natural and thermally modifiedstarch blends from maize and potato. Materials and Methods: The maize and potato starches were combinedin proportions of 1:1 (NSB1) and 1:2 (NSB2) and thermally treated (pregelatinization and retrogradation). Fortheir application as excipients, these thermally treated starch blends were compared to natural starch blends forphysicochemical parameters such as moisture content, water holding capacity, swelling and solubility, and amyloseconcentration. Results and Discussion: The amylose content of the heat-treated gums increased, indicating that itcould be used in colon medication administration. The increase in water holding capacity from 218.13 ± 0.13% to732.27 ± 0.34% demonstrates its promise in hydrogel creation. The moisture percentage of all the blends was inthe range of 10.10 ± 0.03%–15.42 ± 0.03%, which were well within the range specified in Indian Pharmacopoeia.All of the samples’ pH levels were determined to be mildly basic (7.15–7.46). Conclusion: The potato and maizemodified starch blends demonstrated a promising synergistic impact compared to native blends as an adjuvant inthe formulation of various drug delivery systems.